Advancement in Cancer Stem Cell Biology and Precision Medicine—Review Article Head and Neck Cancer Stem Cell Plasticity and the Tumor Microenvironment - Heft Neal, Molly E.; Brenner, J. Chad; Prince, Mark E. P.; Chinn, Steven B. (Frontiers in Cell and Developmental Biology, 2022)
Head and Neck cancer survival has continued to remain around 50% despite treatment advances. It is thought that cancer stem cells play a key role in treatment resistance, metastasis, and recurrence in solid malignancies including head and neck cancer. Initial studies identified cancer stem cell markers including CD44 and ALDH in head and neck malignancies and found that these cells show aggressive features in both in vitro and in vivo studies. Recent evidence has now revealed a key role of the tumor microenvironment in maintaining a cancer stem cell niche. There has now been increasing focus on identifying and targeting the crosstalk between cancer stem cells and surrounding cells within the TME as new therapeutic potential. Here we review the current evidence for cancer stem cell interactions with the TME including endothelial cells, tumor associated fibroblasts, tumor associated monocytes and macrophages, and host immune cells.